BALEH : Heart of Sarawak’s Wilderness - Mohd Azlan, Jayasilan (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd, 2024)
The Baleh region is known for its rugged, unforgiving terrain. Along with a complex network of rivers it is a lost world of fabulous plant and animal life. The forests here harbour towering trees, with delicate orchids and ferns, and are home to countless other species of conservation importance and of endemic species. It is important to create awareness on the links between biodiversity and the provision of these benefits to society. This is crucial, so that the State’s biological resources are valued, protected and sustainably used for the needs of both the present and future generations.